-10=-3(x+3)

Simple and best practice solution for -10=-3(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10=-3(x+3) equation:



-10=-3(x+3)
We move all terms to the left:
-10-(-3(x+3))=0
We calculate terms in parentheses: -(-3(x+3)), so:
-3(x+3)
We multiply parentheses
-3x-9
Back to the equation:
-(-3x-9)
We get rid of parentheses
3x+9-10=0
We add all the numbers together, and all the variables
3x-1=0
We move all terms containing x to the left, all other terms to the right
3x=1
x=1/3
x=1/3

See similar equations:

| 9m-6=3m | | 7/3=x+2/3 | | 6^(4x-2)=12 | | 3x-4=12+9x | | F=2c+32 | | (10+2x)(24+2x)=1176 | | 2(x^2+34x-468)=0 | | 19x+135=4x-30 | | 12x-28=8x+24 | | 10^4x+2=90 | | 11=2/3x+3 | | (x-3)/2=(x-2)/3 | | 2(5x=8)6x=20 | | 180=y+61+57 | | 10+x^2=60 | | t+t+t+t+t=135 | | x-(x*0,41)=59 | | 2t+8=7t-2 | | 6×-7+4x-3=180 | | 2x15,2+8x+7,92=70,56 | | 7x+57=3x+25 | | 7x+48=x+12 | | 7x-9=2x+1. | | x+20=-2x-1 | | 5⋅x√=30 | | (x•x)=23+2x | | 4(y-3)=2(y+1)-6 | | 10w=05 | | x1-x2+3x3=5 | | 4x+4+5x+5=71 | | 3+7•x=40 | | 5x+2=6x-4= |

Equations solver categories